The Role of Sialic Acids in the Establishment of Infections by Pathogens, With Special Focus on Leishmania - Cavalcante, Tainá; Medeiros, Mariana Medina; Mule, Simon Ngao; Palmisano, Giuseppe; Stolf, Beatriz Simonsen (Frontiers in Cellular and Infection Microbiology, 2021)
Carbohydrates or glycans are ubiquitous components of the cell surface which play crucial biological and structural roles. Sialic acids (Sias) are nine-carbon atoms sugars usually present as terminal residues of glycoproteins and glycolipids on the cell surface or secreted. They have important roles in cellular communication and also in infection and survival of pathogens. More than 20 pathogens can synthesize or capture Sias from their hosts and incorporate them into their own glycoconjugates and derivatives. Sialylation of pathogens’ glycoconjugates may be crucial for survival inside the host for numerous reasons. The role of Sias in protozoa such as Trypanosoma and Leishmania was demonstrated in previous studies. This review highlights the importance of Sias in several pathogenic infections, focusing on Leishmania. We describe in detail the contributions of Sias, Siglecs (sialic acid binding Ig-like lectins) and Neuraminidase 1 (NEU 1) in the course of Leishmania infection. A detailed view on the structural and functional diversity of Leishmania-related Sias and host-cell receptors will be provided, as well as the results of functional studies performed with different Leishmania species.